PWE-181 Socio-economic status and lifestyle factors are associated with achalasia risk: a population-based case-control study. (22nd June 2015) - Coleman, HG; Gray, RT; Lau, KW; McCaughey, C; Coyle, PV; Murray, LJ; Johnston, BT
Abstract : Introduction: Achalasia is a neurodegenerative motility disorder of the oesophagus that results in loss of normal lower oesophageal sphincter function. The aetiology of achalasia is very poorly understood. In particular, no lifestyle risk factors have been investigated in relation to achalasia development. The aim of this study was to evaluate the association between the various lifestyle factors and achalasia risk. Method: A population-based case-control study was conducted in Northern Ireland, including n = 151 achalasia cases and n = 117 age- and sex-matched controls. Lifestyle factors were assessed via a face-to-face structured interview. The association between achalasia and lifestyle factors was assessed by unconditional logistic regression, to produce odds ratios (OR) and associated 95% confidence intervals (CI), before and after adjustment for confounders. Results: Individuals who had low-class occupations were at the highest risk of achalasia (OR 1.88 (95% CI: 1.02–3.45), inferring that high class occupation holders have a reduced risk of achalasia. A history of foreign travel, a lifestyle factor linked with upper socio-economic class, was also associated with a reduced risk of achalasia (OR 0.59; 95% CI 0.35–0.99). In contrast, smoking and alcohol consumption – behaviours normally associated with lower socio-economic groups – carried significant reduced risks of achalasia, even after adjustment for socio-economic status. The presence of pets in the house was associated with a two-fold increased risk of achalasia (OR 2.00; 95% CI 1.17–3.42). Conclusion: Achalasia is a disease of inequality, and individuals from low socio-economic backgrounds are at highest risk. This does not appear to be due to corresponding alcohol and smoking behaviours. An observed positive association between pet ownership and achalasia risk may lend support to a role for allergen/infection exposure in achalasia aetiology. Disclosure of interest: None Declared.